Public Services at District Office of Mesjid Raya, Aceh Besar Regency - Muklis; Syafei Ibrahim; Zainur Rozikin (Britain International for Academic Research (BIAR) Publisher, 2024)
Various principles of public service are applied in realizing a service process that is not complicated, so that it can satisfy the community. Based on empirical facts that the principles of public service at District Office of Mesjid Raya, Aceh Besar Regency it is related to simplicity have not been able to create simplicity in the implementation of public services. The problem is how the principles of public service and how the standards of public service at District Office of Mesjid Raya in Aceh Besar Regency. This study uses a qualitative approach with 5 informants consisting of 1 District Head, 1 District Secretary, 1 Head of the Village Community Service Section, 1 Head of the Government Section and 1 population service staff. Data collection was carried out using observation techniques, interviews and documentation studies. The results of the study prove that the principles of public service can be realized through a straightforward service process, so as to satisfy the public. On the other hand, the principles of public service are provided with adequate and definite service places, because the certainty of service places can avoid complaints from the public. Then, security will also create legal certainty as a basis for implementing public services, because without legal certainty, the services provided will be invalid. The public service standards carried out by the district office simplify the requirements set in the service. Then, the service procedure can accelerate the execution of services provided by district office officers, because execution is a process of acceleration in public services. Public service standards at district offices will simplify the registration process, so that public services can be provided in a more timely manner.